2002
DOI: 10.1007/s00383-002-0860-x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine alters enterocyte monolayer permeability via a protein kinase C/Ca 2+ mechanism

Abstract: The activity of phospholipase A(2) (PLA(2)) is elevated in the intestinal epithelia of patients with inflammatory bowel disease. We recently reported that PLA(2) mediates the hydrolysis of phosphatidylcholine (PC) to lysophosphatidylcholine (L-PC) when both are applied to the apical surface of cultures enterocyte monolayers, resulting in increased bacterial translocation (BT) and decreased transepithelial electrical resistance (TEER). However, the mechanism by which the converted L-PC affects tight-junction pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Together, our histology and temperature data suggest a contributing role for LPC in the observed inflammation. This was not unexpected, given the known effect of LPC to increase tight junction permeability [43]. It would therefore be worthwhile to determine the minimum effective dose for LPC.…”
Section: Discussionmentioning
confidence: 94%
“…Together, our histology and temperature data suggest a contributing role for LPC in the observed inflammation. This was not unexpected, given the known effect of LPC to increase tight junction permeability [43]. It would therefore be worthwhile to determine the minimum effective dose for LPC.…”
Section: Discussionmentioning
confidence: 94%
“…Some amphiphilic substances such as lysoPtdCho [47][48][49], dodecylphosphocholine [50], and 2-alkoxy-3-alkylamidopropylphosphocholines [51] enhanced the absorption of hydrophilic agents such as dextran and mannitol by decreasing the integrity of the intercellular barrier formed by cell-to-cell/cell-matrix adhesion. The intestinal absorption of these hydrophilic agents was thought to be mediated by paracellular diffusion, which is the transport process across the intercellular barrier to the basolateral side.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible transport pathways: paracellular and transcellular. LysoPC has been reported to increase the paracellular transport 12 . However, in the present study the paracellular transport was not found.…”
Section: Discussionmentioning
confidence: 99%